Transforming treatment paradigms: Focus on personalized medicine for high‐grade serous ovarian cancer - Pawel Kordowitzki; Britta Lange; Kevin M. Elias; Marcia C. Haigis; Sylvia Mechsner; Ioana Elena Braicu; Jalid Sehouli (CA: A Cancer Journal for Clinicians, 2025)
AbstractHigh‐grade serous ovarian cancer (HGSOC) is the most common and aggressive subtype of ovarian cancer, accounting for approximately 70% of all ovarian cancer cases and contributing significantly to the high mortality rates associated with this disease. Because of the asymptomatic nature of early stage disease, most patients are diagnosed at advanced stages when the cancer has already spread into the abdominal cavity, requiring complex and intensive surgical and chemotherapeutic interventions followed by maintenance therapies. Although a minority of cases are associated with well defined genetic syndromes, specific risk factors and a clear etiology in many cases remain elusive. HGSOC tumors are characterized by a high frequency of somatic gene copy number alterations, often associated with defects in homologous recombination repair of DNA. All attempts to introduce an effective screening for HGSOC to date have been unsuccessful. This review elucidates the complexities surrounding HGSOC and encompasses its etiology, epidemiology, classification, pathogenesis, and the current array of treatment strategies. Understanding molecular underpinnings is crucial for the development of targeted therapies and personalized multimodal treatment approaches in centralized therapeutic structures. This review also examines the importance of the tumor microenvironment. In addition, the authors' objective is to underscore the critical importance of placing the patient's perspective and diversity at the forefront of therapeutic strategies, thereby fostering a genuinely participatory decision‐making process and ultimately improving patient quality of life.